2008
DOI: 10.1002/cjce.5450840117
|View full text |Cite
|
Sign up to set email alerts
|

A Short Note About Energy-Efficiency Performance of Thermally Coupled Distillation Sequences

Abstract: THE CANADIAN JOURNAL OF CHEMICAL ENGINEERING 139R&D NOTE D istillation is a widely used separation method in the process industries and it is the largest energy consumer among individual process units. Improvement of energy efficiency in distillation systems is still an active research field. Among the issues concerned with the improvement of energy efficiency of distillation systems, the optimal design and synthesis of multicomponent distillation schemes is still one of the most challenging problems. For opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Recent research efforts have been conducted to understand the operational properties of thermally coupled configurations. The works of Wolff and Skogestad, 1995;Abdul-Mutalib and Smith, 1998;Hernández and Jiménez, 1999b;Serra et al, 1999;Serra et al, 2001;Jiménez et al, 2001;Segovia -Hernández et al, 2002a;Segovia -Hernández et al, 2002b;Serra et al, 2003;Segovia -Hernández et al, 2004;SegoviaHernández et al, 2005a;Segovia -Hernández et al, 2005b;Segovia -Hernández et al, 2005c;Alcántara -Ávila et al, 2006;Segovia -Hernández et al, 2006a;Segovia -Hernández et al, 2006b;Segovia -Hernández et al, 2007a;SegoviaHernández et al, 2007b, among others, have shown that some of these integrated options are controllable, so that the predicted savings in both energy and capital would probably not be obtained at the expense of operational and control problems.…”
Section: Introductionmentioning
confidence: 96%
“…Recent research efforts have been conducted to understand the operational properties of thermally coupled configurations. The works of Wolff and Skogestad, 1995;Abdul-Mutalib and Smith, 1998;Hernández and Jiménez, 1999b;Serra et al, 1999;Serra et al, 2001;Jiménez et al, 2001;Segovia -Hernández et al, 2002a;Segovia -Hernández et al, 2002b;Serra et al, 2003;Segovia -Hernández et al, 2004;SegoviaHernández et al, 2005a;Segovia -Hernández et al, 2005b;Segovia -Hernández et al, 2005c;Alcántara -Ávila et al, 2006;Segovia -Hernández et al, 2006a;Segovia -Hernández et al, 2006b;Segovia -Hernández et al, 2007a;SegoviaHernández et al, 2007b, among others, have shown that some of these integrated options are controllable, so that the predicted savings in both energy and capital would probably not be obtained at the expense of operational and control problems.…”
Section: Introductionmentioning
confidence: 96%
“…With the recent strong upward trend in the cost of energy, there is considerable renewed interest in determining energy efficient distillation designs. Many studies have focused on the energy savings for anhydrous ethanol production. , Considering schemes of a thermally integrated extractive distillation process, a new system consisting of a fully thermally coupled distillation column was presented for the improvement of distillation column efficiency, and a comparative study of the energy-efficiency performance between conventional distillation sequences and thermally coupled distillation arrangements (TCDS) was conducted recently …”
Section: Introductionmentioning
confidence: 99%
“…19,20 Considering schemes of a thermally integrated extractive distillation process, a new system consisting of a fully thermally coupled distillation column was presented for the improvement of distillation column efficiency, 21 and a comparative study of the energy-efficiency performance between conventional distillation sequences and thermally coupled distillation arrangements (TCDS) was conducted recently. 22 In order to reduce the energy consumption for the production of anhydrous ethanol, a novel extractive distillation configuration with three columns is presented in this paper. The process is simulated on the Aspen Plus platform.…”
Section: Introductionmentioning
confidence: 99%
“…ITCDICs are quite different from conventional distillation columns (CDICs), in which the reboiler and the condenser are no longer needed. And they have received increasing attention since the 1990s . Compared with CDICs, ITCDICs have the capability of reducing energy consumption up to 30% or even more and also have the advantage of high separation efficiency over CDICs …”
Section: Introductionmentioning
confidence: 99%